Tax competition and tax coordination in the European Union: A survey - Christian Keuschnigg; Simon Loretz; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2014)
This survey summarizes the state and development of European tax policy, in particular discussing the harmonization progress in direct as well as indirect taxes. Based on an overview over the theoretical and empirical literature on tax competition, we further ask whether increased tax coordination is necessary to prevent a race to the bottom. We show that theoretical predictions on the outcome of tax competition are ambiguous, and the empirical evidence in this regard is inconclusive as well. This, in turn, gives rise to an only limited scope of stronger tax harmonization.
Keywords: H87; H77; 330; Tax competition; Tax coordination; European economic integration